PENGARUH KEPUASAN PELANGGAN SEBAGAI PEMEDIASI UNTUK MEMPERTAHANKAN LOYALITAS PELANGGAN PADA LARISSA AESTHETIC CENTER SEMARANG - Herry Widodo; Vera Lusiana (LPPM STIE DHARMAPUTRA SEMARANG, 2022)
ABSTRACTThe purpose of this study was to analyze the effect of work stress and work environment on organizational citizenship behavior with organizational commitment as a mediating variable. The population of this study was all employees of the Office of Cooperatives and Micro Enterprises of Central Java Province, totaling 103 people. Samples were taken by all members of the population with the census method. Methods of data analysis using regression analysis and data processing using SPSS. The results of hypothesis testing show that work stress has a significant negative effect on organizational commitment. The work environment has a significant positive effect on organizational commitment. Organizational commitment has a significant positive effect on organizational citizenship behavior. Job stress has a significant negative effect on organizational citizenship behavior. The work environment has a significant positive effect on organizational citizenship behavior. The results of the analysis of mediating variables using the Sobel test found that organizational commitment can mediate work stress on organizational citizenship behavior. Organizational commitment can mediate the influence of the work environment on organizational citizenship behavior. Keywords: work stress, work environment, organizational commitment, organizational citizenship behavior ABSTRAKPenelitian ini bertujuan untuk menganalisis pengaruh kualitas layanan dan kepercayaan pelanggan terhadap loyalitas pelanggan yang dimediasi oleh kepuasan pelanggan. Jenis penelitian ini adalah penelitian deskriptif. Populasi dari penelitian ini adalah seluruh konsumen Larissa Aesthetic Center Semarang. Sampel dalam penelitian ini ditentukan dengan rumus Slovin dan didapatkan sebanyak 100 responden. Teknik pengambilan sampel menggunakan metode purposive sampling. Analisis data menggunakan program SPSS 21 dan AMOS versi 21. Hasil penelitian ini menunjukkan Kualitas Layanan berpengaruh positif signifikan terhadap Kepuasan Pelanggan Larissa Aesthetic Center Semarang. Kepercayaan Pelanggan berpengaruh positif tidak signifikan terhadap Kepuasan Pelanggan Larissa Aesthetic Center Semarang. Kualitas Layanan berpengaruh positif tidak signifikan terhadap Loyalitas Pelanggan Larissa Aesthetic Center Semarang. Kepercayaan Pelanggan berpengaruh positif signifikan terhadap Loyalitas Pelanggan Larissa Aesthetic Center Semarang. Kepuasan Pelanggan berpengaruh positif signifikan terhadap Loyalitas Pelanggan Larissa Aesthetic Center Semarang. Adanya hubungan timbal balik antara Kualitas Layanan dengan Kepercayaan Pelanggan. Kata Kunci : Kualitas Layanan, Kepercayaan Pelanggan, Kepuasan Pelanggan, Loyalitas Pelanggan